2008
DOI: 10.4065/83.5.566
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Lyme Disease

Abstract: Lyme disease is the most common tick-borne disease in the United States. This review details the risk factors, clinical presentation, treatment, and prophylaxis for the disease. Information was obtained from a search of the PubMed and MEDLINE databases (keyword: Lyme disease) for articles published from August 31, 1997, through September 1, 2007. Approximately 20,000 cases of Lyme disease are reported annually. Residents of the coastal Northeast, northwest California, and the Great Lakes region are at highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…This infection is a global health concern and is associated with numerous cardiologic, dermatologic, rheumatologic neurologic, and psychiatric manifestations (Bratton et al, 2008). Only a few epidemiologic studies have evaluated the frequency of antibodies to Bb in psychiatric patients; one study found only 1/517 (0.2%) of all adult psychiatric patients had Lyme titer seropositivity (Nadelman et al, 1997) and the other larger study found that 322/926 (35%) of psychiatric inpatients had seropositivity to antibodies to Bb (Hajek et al, 2002).…”
Section: Dear Editorsmentioning
confidence: 99%
“…This infection is a global health concern and is associated with numerous cardiologic, dermatologic, rheumatologic neurologic, and psychiatric manifestations (Bratton et al, 2008). Only a few epidemiologic studies have evaluated the frequency of antibodies to Bb in psychiatric patients; one study found only 1/517 (0.2%) of all adult psychiatric patients had Lyme titer seropositivity (Nadelman et al, 1997) and the other larger study found that 322/926 (35%) of psychiatric inpatients had seropositivity to antibodies to Bb (Hajek et al, 2002).…”
Section: Dear Editorsmentioning
confidence: 99%
“…Mild systemic symptoms like low-grade fever and chills might be present. EM in the United States is often associated with more prominent signs of inflammation, as compared to that in Europe [1-4]. This case report illustrates that erythemas caused by other pathogens might resemble this clinical picture, thus a false diagnosis may be made which may complicate and prolong the disease process and prevent adequate therapy.…”
Section: Introductionmentioning
confidence: 95%
“…Among many clinicians, laminary spreading erythemas often lead to the diagnosis of a tick bite-associated erythema migrans (EM), a symptom of early localized infection with Borrelia burgdorferi (sensu lato) [1,2]. As the development of an immunologic response to this infection usually takes 4 to 6 weeks and the incubation period for EM is typically 7 to 14 days, early Lyme borreliosis often presents itself with a negative serology [3,4]. In addition, tick bites are not always described or remembered by the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Early LD is diagnosed in the clinic by recognition of the EM rash, other associated symptoms, and a compatible exposure history (11,12). However, the diagnosis can be difficult, as 5 to 30% of patients do not present with an EM rash (10,12) and early-stage symptoms may be completely lacking or nonspecific (13).…”
mentioning
confidence: 99%
“…However, the diagnosis can be difficult, as 5 to 30% of patients do not present with an EM rash (10,12) and early-stage symptoms may be completely lacking or nonspecific (13). Laboratory confirmation of clinical diagnosis is performed using serology.…”
mentioning
confidence: 99%